Om konstig Østersavl ved de danske Kyster. Foredrag, den 30te Januar 1861. - Eschricht, Professor (Tidsskrift for Landøkonomi, 2018)
Om konstig Østersavl ved de danske Kyster. Foredrag, den 30te Januar 1861.